Energy Market in Contemporary International Relations: Main Threats and Challenges - Justyna Misiągiewicz (Barometr Regionalny, 2022)
The main objective of the present study is to analyze the main challenges and threats to the international energy market in the context of transformations in international relations. It will be possible thanks to a comprehensive explanatory and predictive analysis. The study verifies the research hypothesis that the evolution of energy security and the prospects for its development largely result from the relations on the global energy market. Analyses of energy security issues take into account long-term development trends as well as unpredictable events related to the functioning of international economic relations. Thus, the phenomena resulting from the dynamics of the international environment are gaining in importance. New energy systems and new technologies can lead the world towards new challenges and threats. The methodological framework of the conducted research includes research methods appropriate to the science of international relations. The factor method was useful in identifying the determinants of energy security market transformation in the contemporary world. The predictive analysis turned out to be helpful in the part of the thesis on the prospects for the development of the energy market. The research techniques used in the article include the analysis of literature, documents and statistical data.